Price Performance of IPOs in Indian Stock Market - Chopra, Rohini Inder (My University, 2009)
The present study intends to examine the price performance of the Indian IPOs listed on NSE, using a sample of IPOs that tapped the NSE market during 1999-2008 by taking in consideration of their prices. The short run as well as long run analysis of their price performance have been done by taking the gap of time intervals of 1 weak, 1month, 3months, 6months and 1year, 2years, 3years respectively. In addition to that an analysis has been conducted to know the influence of the factors viz. subscription level, Issue size, Listing Lead time and Age, on the price performance of the IPOs. The study shows that underpricing is present in the Indian Capital market. Also, underpricing is more prevalent in the short run than in the long run. The study further shows that IPOs come to their intrinsic value over a period of time. The regulatory framework of IPOs with special reference to SEBI guidelines has also been done.
M.Phil (Economics)
Keywords: IPO; Price Performance; Underpricing